High-nickel ternary positive electrode material as well as preparation method and application thereof

By setting a lithium peroxide cladding layer on the surface of the high-nickel ternary positive electrode material, the problem of structural damage and cycle performance degradation during the charging and discharge process is solved, and the stability and capacity performance of the material are improved.

CN119324215AActive Publication Date: 2025-01-17GUANGDONG BRUNP RECYCLING TECH CO LTD +1

Patent Information

Application Number
CN202411462124.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-17
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

High-nickel ternary cathode materials are prone to structural damage during charging and discharging, resulting in capacity attenuation and degradation of cycling performance, and existing doping and protective layer improvement methods may affect material capacity.

Method used

The lithium peroxide cladding layer is provided on the surface of the high-nickel ternary positive electrode material, and a lithium hydroxide pre-clad layer is formed by calcining and aqueous solution treatment, and converted into a lithium peroxide cladding layer in an ozone atmosphere to enhance the circulation performance of the material And achieve lithium supplementation effect.

Benefits of technology

The circulation and capacity performance of high-nickel ternary cathode materials are improved, the material capacity damage is avoided, and the lithium-nickel mixed discharge degree is reduced, which enhances the stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119324215A_ABST
    Figure CN119324215A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries. The invention provides a high-nickel ternary positive electrode material and a preparation method and application thereof, the high-nickel ternary positive electrode material comprises a high-nickel main material and a coating layer arranged on the surface of the high-nickel main material, and the coating layer comprises lithium peroxide. Through lithium peroxide coating, the protection and isolation effects of a coating layer can be achieved, the cycle performance is improved, the lithium supplementing effect can be achieved, and capacity damage cannot be caused to the high-nickel main material. According to the preparation method, peroxide is introduced in the process of forming the high-nickel main material through high-temperature calcination, the mixing degree of lithium and nickel in the high-nickel and ultra-high-nickel ternary main material is effectively reduced, the obtained high-nickel main material is washed in a lithium-containing aqueous solution, lithium hydroxide coating is achieved while lithium carbonate is washed away, damage of water to the main material is inhibited, and the high-nickel and ultra-high-nickel ternary main material is obtained. A rock salt phase protection layer is generated on the surface of the main material, so that the cycling stability of the material is further enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a high-nickel ternary positive electrode material and a preparation method and application thereof. Background Art

[0002] With the transformation of the global energy structure and the enhancement of environmental protection awareness, the rapid development of power vehicles and energy storage technology has become an important force in promoting the green economy. In this context, lithium-ion batteries, as the core components of energy storage and conversion, have shown broad application prospects in many fields such as electric vehicles, portable electronic devices, smart grids, and aerospace due to their significant advantages such as high energy density, long cycle life, no memory effect, and environmental friendliness.

[0003] Lithium-ion batteries are mainly composed of key components such as positive electrode, negative electrode, electrolyte and diaphragm. The positive electrode material is the main embedding and de-embedding site of lithium ions, and its performance directly affects the overall performance of the battery. According to the different positive electrode materials, lithium-ion batteries can be divided into various systems such as lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate and ternary materials. Among them, ternary materials (i.e. lithium nickel cobalt manganese oxide / lithium nickel cobalt aluminum oxide) have been rapidly developed in the field of power vehicles due to their excellent comprehensive performance, especially high energy density characteristics.

[0004] By adjusting the proportion of nickel, the energy density of the ternary cathode material can be significantly improved. However, as the nickel content is further increased, the process of gradually turning to high-nickel ternary materials (Ni content is 60% to 90%) or ultra-high nickel ternary materials (Ni content> 90%) also brings some problems. For example, in the actual charging and discharging process, due to the repeated insertion and extraction of lithium ions, it is easy to cause the destruction of the material structure, which in turn causes the problem of capacity decay and cycle performance degradation. In addition, the surface chemical activity of high-nickel materials is high, and it is easy to react with the electrolyte to form a solid electrolyte interface film (SEI), which not only consumes active lithium, but also increases the internal resistance of the battery, affecting the performance and life of the battery.

[0005] In response to the above problems of high-nickel ternary materials, researchers have proposed optimization methods using high-valent element doping and dense protective layer coating. However, although high-valent element doping can enhance the structural stability of the material, excessive doping may introduce new defects and affect the material's electrochemical properties such as capacity; and although dense protective layer coating can effectively isolate the material from direct contact with the electrolyte, the presence of the coating layer often leads to a decrease in the proportion of positive electrode materials, which in turn causes a decrease in capacity.

[0006] Therefore, how to find a solution that can effectively improve the cycle performance of ultra-high nickel ternary positive electrode materials without damaging the material capacity is an urgent problem to be solved in this field. Summary of the invention

[0007] In view of the problems existing in the prior art, the purpose of the present invention is to provide a high-nickel ternary positive electrode material and its preparation method and use, including a high-nickel main material and a coating layer arranged on the surface of the high-nickel main material, wherein the coating layer includes lithium peroxide. The present invention can not only play a protective and isolating role of the coating layer and improve the cycle performance, but also produce a lithium supplement effect, and will not cause capacity damage to the high-nickel main material through lithium peroxide coating.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a high-nickel ternary positive electrode material, including a main material, wherein the chemical formula of the main material includes LiNi x Co y Mn z O2, wherein x≥0.6, y>0, z>0, x+y+z=1; a coating layer is provided on the surface of the main material, and the coating layer includes lithium peroxide.

[0010] The present invention arranges a coating layer including lithium peroxide on the surface of the high-nickel main material. The lithium peroxide coating can not only play a protective and isolating role of the coating layer, but also improve the cycle performance. The lithium peroxide can be decomposed during the charging process, thereby increasing the charging capacity and achieving a lithium replenishment effect. In this way, not only will the capacity of the high-nickel main material not be damaged, but the capacity performance of the obtained high-nickel ternary positive electrode material can also be improved.

[0011] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0012] As a preferred technical solution of the present invention, the main material is an ultra-high nickel ternary positive electrode material, x>0.9.

[0013] In a second aspect, the present invention provides a method for preparing the high-nickel ternary positive electrode material according to the first aspect, the preparation method comprising:

[0014] (1) Ni x Co y Mn z (OH)2, mixed with lithium source and peroxide, calcined to obtain the main material LiNi x Co y Mn z O2, where x≥0.6, y>0, z>0, x+y+z=1;

[0015] (2) The main material LiNi x Co y Mn zO2 is mixed with lithium-containing aqueous solution, and the main material LiNi x Co y Mn z A lithium hydroxide pre-coating layer is formed on the surface of O2 to obtain a pre-coating body;

[0016] (3) The obtained pre-coated body is heat-treated in an ozone-containing atmosphere to convert the lithium hydroxide pre-coating layer into a lithium peroxide coating layer, thereby obtaining a high-nickel ternary positive electrode material.

[0017] In the preparation method of the present invention, the peroxide is introduced during the high-temperature calcination process in step (1), thereby reducing the Ni content in the material. 2+ , thereby effectively reducing the degree of lithium-nickel mixing in high-nickel and ultra-high-nickel ternary main materials, and further enhancing the material's cycle performance; in step (2), mixing in a lithium-containing aqueous solution has a water washing effect, while washing away the lithium carbonate on the surface of the main material, it can also achieve lithium hydroxide coating through the lithium-containing compound, inhibiting the damage of water to the main material, and generating a rock salt phase protective layer on the surface of the main material, further enhancing the material's cycle stability; the heat treatment in step (3) is low-temperature sintering, and an ozone-containing atmosphere is used to convert the lithium hydroxide on the surface into a lithium peroxide coating layer. The reaction principle includes: 2LiOH+O3→Li2O2+H2O+O2, which can not only play the role of a coating layer, but also replenish lithium for the material, that is, the lithium replenishment principle during the charging process includes: Li2O2→2Li + +O2+2e - , thereby improving the capacity of the resulting high-nickel ternary positive electrode material.

[0018] It should be noted that, since the residual lithium of the low-nickel ternary material (x<0.6) is very low, washing it in a lithium-containing aqueous solution in step (2) of the preparation method of the present invention will affect the material properties.

[0019] As a preferred technical solution of the present invention, in step (1), the precursor Ni x Co y Mn z The ratio of the molar amount of (OH)2 to the molar amount of lithium element in the lithium source is 1:(1-1.2).

[0020] As a preferred technical solution of the present invention, in step (1), the lithium source includes any one of lithium oxalate, lithium carbonate, lithium hydroxide monohydrate, lithium acetate or lithium citrate.

[0021] As a preferred technical solution of the present invention, in step (1), the precursor Ni x Co y Mn z The ratio of the molar amount of (OH)2 to the molar amount of the peroxide is 1:(0.001-0.01).

[0022] As a preferred technical solution of the present invention, in step (1), the peroxide includes any one of lithium peroxide, sodium peroxide, nickel peroxide, strontium peroxide, or barium peroxide.

[0023] As a preferred technical solution of the present invention, in step (1), the calcination temperature is 700-1100° C. and the calcination time is 10-20 hours.

[0024] As a preferred technical solution of the present invention, in step (2), the concentration of lithium element in the lithium-containing aqueous solution is 0.5 to 5 mol / L.

[0025] As a preferred technical solution of the present invention, the lithium-containing aqueous solution and the main material LiNi x Co y Mn z The mass ratio of O2 is (0.1~1):1.

[0026] As a preferred technical solution of the present invention, the method for preparing the lithium-containing aqueous solution in step (2) comprises adding the lithium-containing compound into water at a temperature of 0 to 40° C. and stirring at 100 to 300 rpm for 2 to 20 minutes.

[0027] As a preferred technical solution of the present invention, the lithium-containing compound includes at least one of lithium oxalate, lithium oxide, lithium hydroxide monohydrate, lithium acetate or lithium citrate.

[0028] As a preferred technical solution of the present invention, in step (2), the main material LiNi x Co y Mn z The mixing time of O2 and the lithium-containing aqueous solution is 10 to 60 minutes.

[0029] As a preferred technical solution of the present invention, in step (2), the main material LiNi x Co y Mn z After O2 is mixed with the lithium-containing aqueous solution, the mixed solution is centrifuged at 40-60 Hz for 0.5-1.5 hours to obtain a centrifuge; the centrifuge is vacuum dried at 100-180°C for 2-20 hours, and then passed through a 280-320 mesh sieve to obtain a sieve-less material; the sieve-less material obtained is used as the pre-coated body to perform step (3).

[0030] As a preferred technical solution of the present invention, in step (3), in the ozone-containing atmosphere, the volume of ozone accounts for 1% to 10%.

[0031] As a preferred technical solution of the present invention, the temperature of the heat treatment is 200-400° C. and the time is 5-10 hours.

[0032] In a third aspect, the present invention provides a positive electrode plate, wherein the positive electrode plate contains the high-nickel ternary positive electrode material described in the first aspect.

[0033] In a fourth aspect, the present invention provides a battery, wherein the battery comprises the positive electrode sheet described in the third aspect.

[0034] Compared with the prior art solutions, the present invention has at least the following beneficial effects:

[0035] The present invention arranges a coating layer including lithium peroxide on the surface of a high-nickel main material. The lithium peroxide coating can not only play a protective and isolating role of the coating layer, thereby improving the cycle performance, but also produce a lithium replenishing effect. It will not cause capacity damage to the high-nickel main material, but also improve the capacity performance of the resulting high-nickel ternary positive electrode material.

[0036] In the preparation method of the present invention, by introducing peroxide during the high-temperature calcination process, the degree of mixing of lithium and nickel in high-nickel and ultra-high-nickel ternary main materials is effectively reduced, and the cycle performance of the material is further enhanced; by mixing in a lithium-containing aqueous solution, a water washing effect is achieved, and while washing away the lithium carbonate on the surface of the main material, lithium hydroxide can be coated by the lithium-containing compound, thereby inhibiting the damage of water to the main material, and a rock salt phase protective layer is generated on the surface of the main material, further enhancing the cycle stability of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a SEM test image of the high-nickel ternary material obtained in Example 1;

[0038] Figure 2 This is the XRD test diagram of the high nickel ternary material obtained in Example 1;

[0039] Figure 3 It is a cycle performance test chart of the ternary materials obtained in Example 1, Example 5, Example 7 and Comparative Example 2. DETAILED DESCRIPTION

[0040] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the implementation methods and examples are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0041]

High nickel ternary cathode material

[0042] In some specific embodiments, the present invention provides a high-nickel ternary positive electrode material, including a main material, wherein the chemical formula of the main material includes LiNi x Co y Mn zO2, wherein x≥0.6, y>0, z>0, x+y+z=1; a coating layer is provided on the surface of the main material, and the coating layer includes lithium peroxide.

[0043] In one embodiment, the chemical formula of the main material is LiNi x Co y Mn z In O2, x≥0.6, for example, x can be 0.6, 0.63, 0.65, 0.68, 0.7, 0.73, 0.75, 0.78, 0.8, 0.82, 0.85, 0.88, 0.9, 0.92, 0.94 or 0.96, etc., preferably >0.9 (ultra-high nickel ternary positive electrode material); y>0, for example, y can be 0.01, 0.05, 0.08, 0. 1, 0.13, 0.15, 0.18, 0.2, 0.22, 0.25, 0.28, 0.3, 0.32, 0.35 or 0.39, etc.; z>0, for example, z can be 0.01, 0.05, 0.08, 0.1, 0.13, 0.15, 0.18, 0.2, 0.22, 0.25, 0.28, 0.3, 0.32, 0.35 or 0.39, etc.

[0044]

Preparation method of high nickel ternary positive electrode material

[0045] In some specific embodiments, the present invention provides a method for preparing the high-nickel ternary positive electrode material described in the above embodiment, the preparation method comprising:

[0046] (1) Ni x Co y Mn z (OH)2, mixed with lithium source and peroxide, calcined to obtain the main material LiNi x Co y Mn z O2, where x≥0.6, y>0, z>0, x+y+z=1;

[0047] (2) The main material LiNi x Co y Mn z O2 is mixed with lithium-containing aqueous solution, and the main material LiNi x Co y Mn z A lithium hydroxide pre-coating layer is formed on the surface of O2 to obtain a pre-coating body;

[0048] (3) The obtained pre-coated body is heat-treated in an ozone-containing atmosphere to convert the lithium hydroxide pre-coating layer into a lithium peroxide coating layer, thereby obtaining a high-nickel ternary positive electrode material.

[0049] In one embodiment, in step (1), the precursor Ni x Co y Mn z The ratio of the molar amount of (OH)2 to the molar amount of lithium element in the lithium source is 1:(1-1.2), for example, 1:1, 1:1.03, 1:1.05, 1:1.08, 1:1.1, 1:1.13, 1:1.15, 1:1.18 or 1:1.2, etc.

[0050] In one embodiment, in step (1), the lithium source includes any one of lithium oxalate, lithium carbonate, lithium hydroxide monohydrate, lithium acetate or lithium citrate.

[0051] In one embodiment, in step (1), the precursor Ni x Co y Mn z The ratio of the molar amount of (OH)2 to the molar amount of the peroxide is 1:(0.001-0.01), for example, 1:0.001, 1:0.002, 1:0.003, 1:0.004, 1:0.005, 1:0.006, 1:0.007, 1:0.008, 1:0.009 or 1:0.01, etc.

[0052] In one embodiment, in step (1), the peroxide includes any one of lithium peroxide, sodium peroxide, nickel peroxide, strontium peroxide, or barium peroxide.

[0053] In one embodiment, in step (1), the calcination temperature is 700-1100°C, for example 700°C, 730°C, 750°C, 780°C, 800°C, 820°C, 850°C, 880°C, 900°C, 930°C, 950°C, 980°C, 1000°C, 1030°C, 1050°C, 1080°C or 1100°C, and the calcination time is 10-20h, for example 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h or 20h, etc.

[0054] In one embodiment, in step (2), the concentration of lithium element in the lithium-containing aqueous solution is 0.5-5 mol / L, for example, 0.5 mol / L, 0.8 mol / L, 1 mol / L, 1.3 mol / L, 1.5 mol / L, 1.8 mol / L, 2 mol / L, 2.3 mol / L, 2.5 mol / L, 2.8 mol / L, 3 mol / L, 3.3 mol / L, 3.5 mol / L, 3.8 mol / L, 4 mol / L, 4.2 mol / L, 4.5 mol / L, 4.8 mol / L or 5 mol / L, etc.

[0055] In one embodiment, in step (2), the lithium-containing aqueous solution and the main material LiNi x Co y Mn z The mass ratio of O2 is (0.1-1):1, for example 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1 or 1:1, etc., but is not limited to the listed values, and other listed values ​​within the above numerical range are also applicable.

[0056] In one embodiment, the method for preparing the lithium-containing aqueous solution in step (2) comprises adding the lithium-containing compound to water at a temperature of 0 to 40° C., such as 0° C., 5° C., 10° C., 15° C., 20° C., 25° C., 30° C., 35° C. or 40° C., etc., preferably 0 to 20° C., at 100 to 300 rpm, such as 100 rpm, 130 rpm, 150 rpm, 180 rpm, 200 rpm, 230 rpm, 250 rpm, 280 rpm or 300 rpm, etc., and stirring for 2 to 20 min, such as 2 min, 5 min, 8 min, 10 min, 12 min, 14 min, 16 min, 18 min or 20 min, etc.

[0057] In one embodiment, the lithium-containing compound includes at least one of lithium oxalate, lithium oxide, lithium hydroxide monohydrate, lithium acetate or lithium citrate.

[0058] In one embodiment, in step (2), the main material LiNi x Co y Mn z The mixing time of O2 and the lithium-containing aqueous solution is 10 to 60 minutes, for example, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes or 60 minutes.

[0059] In one embodiment, in step (2), the main material LiNi x Co y Mn zAfter O2 is mixed with the lithium-containing aqueous solution, the mixed solution is centrifuged at 40-60 Hz, such as 40 Hz, 45 Hz, 50 Hz, 55 Hz or 60 Hz, for 0.5-1.5 h, such as 0.5 h, 0.8 h, 1 h, 1.2 h or 1.5 h, to obtain a centrifuge; the centrifuge is vacuum dried at 100-180°C, such as 100°C, 120°C, 140°C, 160°C or 180°C, for 2-20 h, such as 2 h, 4 h, 6 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h or 20 h, and then passed through a 280-320 mesh sieve, such as 280 mesh, 290 mesh, 300 mesh, 310 mesh or 320 mesh, to obtain a sieve undersize; the sieve undersize obtained is used as the pre-encapsulated body for step (3).

[0060] In one embodiment, in step (3), in the ozone-containing atmosphere, the volume of ozone accounts for 1% to 10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.

[0061] In one embodiment, the ozone-containing atmosphere is a mixed atmosphere of ozone and oxygen.

[0062] In one embodiment, the heat treatment temperature is 200-400°C, for example 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 320°C, 340°C, 360°C, 380°C or 400°C, and the time is 5-10h, for example 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h or 10h, etc.

[0063] It should be noted that due to space limitations and to avoid redundancy, the present invention does not list all point values ​​within the above numerical range one by one, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0064]

Positive electrode

[0065] In some specific embodiments, the present invention provides a positive electrode plate, which contains the high-nickel ternary positive electrode material described in the above embodiment.

[0066] In one embodiment, the positive electrode plate includes a positive electrode collector and a positive electrode active layer disposed on the positive electrode collector, the positive electrode active layer includes a positive electrode active material, the positive electrode active material includes the high-nickel ternary positive electrode material, and also includes a positive electrode conductor and a positive electrode binder.

[0067] [Cathode current collector]

[0068] The present invention does not impose any specific restrictions on the specific selection of the positive electrode current collector. Those skilled in the art can reasonably select and adjust it according to actual needs. For example:

[0069] In one embodiment, the positive electrode current collector includes a first metal foil or a first composite current collector.

[0070] In one embodiment, the first metal foil comprises aluminum foil or carbon-coated aluminum foil.

[0071] In one embodiment, the first composite current collector includes a first polymer material base layer and a first metal layer formed on the first polymer material base layer.

[0072] In one embodiment, the metal material of the first metal layer includes aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver or silver alloy.

[0073] In one embodiment, the material of the first polymer material base layer includes polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene or polyethylene.

[0074] [Positive electrode conductive agent and positive electrode binder]

[0075] The present invention does not impose any specific restrictions on the types of the positive electrode conductive agent and the positive electrode binder and their proportions in the active layer. Those skilled in the art can reasonably select and adjust them according to actual needs. For example:

[0076] In one embodiment, the positive electrode conductive agent includes at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers.

[0077] In one embodiment, the positive electrode binder includes at least one of polyvinylidene fluoride, styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol, sodium alginate, polymethacrylic acid or carboxymethyl chitosan.

[0078] [Making method of positive electrode sheet]

[0079] The present invention does not impose any specific restrictions on the method for manufacturing the positive electrode sheet. Those skilled in the art can reasonably select and adjust it according to actual needs. For example:

[0080] In one embodiment, the method for manufacturing the positive electrode sheet includes mixing a positive electrode active material, a positive electrode conductor, a positive electrode binder and a positive electrode solvent to obtain a positive electrode slurry; coating the positive electrode slurry on a positive electrode collector, and drying to obtain a positive electrode sheet.

[0081] In one embodiment, the cathode solvent includes N-methylpyrrolidone.

[0082]

Battery

[0083] In some specific embodiments, the present invention provides a battery, wherein the battery comprises the positive electrode sheet described in the above embodiments.

[0084] In one embodiment, the battery includes the positive electrode sheet, as well as a negative electrode sheet, a separator and an electrolyte.

[0085] [Negative electrode]

[0086] The present invention does not impose any specific restrictions on the specific selection of the negative electrode sheet and its manufacturing method. Those skilled in the art can reasonably select and adjust according to actual needs. For example:

[0087] In one embodiment, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on the negative electrode current collector, wherein the negative electrode active layer includes a negative electrode active material, a negative electrode conductive agent and a negative electrode binder.

[0088] In one embodiment, the negative electrode current collector includes a second metal foil or a second composite current collector.

[0089] In one embodiment, the second metal foil comprises copper foil.

[0090] In one embodiment, the second composite current collector includes a second polymer material base layer and a second metal layer formed on the second polymer material base layer.

[0091] In one embodiment, the metal material of the second metal layer includes copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver or silver alloy.

[0092] In one embodiment, the material of the second polymer material base layer includes polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene or polyethylene.

[0093] In one embodiment, the negative electrode active material includes artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, and the like.

[0094] In one embodiment, the silicon-based material includes at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, or silicon alloys.

[0095] In one embodiment, the tin-based material includes at least one of elemental tin, tin oxide compounds or tin alloys.

[0096] In one embodiment, the negative electrode conductive agent includes at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers.

[0097] In one embodiment, the negative electrode binder includes at least one of styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol, sodium alginate, polymethacrylic acid and carboxymethyl chitosan.

[0098] In one embodiment, the method for manufacturing the negative electrode sheet includes mixing a negative electrode active material, a negative electrode conductive agent, a negative electrode binder and a negative electrode solvent to form a negative electrode slurry; coating the negative electrode slurry on a negative electrode collector, and obtaining a negative electrode sheet after drying, cold pressing and other processes.

[0099] In one embodiment, the negative electrode solvent includes N-methylpyrrolidone.

[0100] [Diaphragm]

[0101] The present invention has no particular restrictions on the type and selection of the separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected, for example:

[0102] In one embodiment, the material of the separator includes at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride.

[0103] In one embodiment, the separator is a single-layer film or a multi-layer composite film.

[0104] In one embodiment, the separator is a multi-layer composite film, and the materials of each layer are the same or different.

[0105] [Electrolytes]

[0106] The present invention has no particular restrictions on the type and selection of electrolytes, which can be selected according to needs, for example:

[0107] In one embodiment, the electrolyte is a solid electrolyte or a liquid electrolyte (ie, an electrolyte solution).

[0108] In one embodiment, the electrolyte is an electrolyte solution including an electrolyte salt and a dissolving solvent.

[0109] In one embodiment, the electrolyte salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorophosphate, lithium difluorobisoxalatophosphate, or lithium tetrafluorooxalatophosphate.

[0110] In one embodiment, the dissolving solvent includes at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0111] In one embodiment, the electrolyte also includes additives; the additives include negative electrode film-forming additives and / or positive electrode film-forming additives, and may also include additives that can improve certain performance of the battery, such as additives that improve the overcharge performance of the battery, additives that improve the high temperature performance of the battery, and additives that improve the low temperature performance of the battery.

[0112] Example 1

[0113] This embodiment provides a high-nickel ternary material, including a main material, wherein the chemical formula of the main material includes LiNi 0.93 Co 0.03 Mn 0.04 O2, a coating layer is provided on the surface of the main material, and the coating layer is lithium peroxide;

[0114] The preparation method of the high-nickel ternary material comprises:

[0115] (1) Take 20 kg of nickel-cobalt-manganese hydroxide precursor Ni 0.93 Co 0.03 Mn 0.04 (OH)2 was mechanically mixed with 9.24 kg of lithium source lithium hydroxide monohydrate and 19.8 g of lithium peroxide lithium peroxide using a plowshare mixer at a speed of 50 Hz for 30 min, and then the mixture was calcined at 800 ° C for 15 h in an oxygen atmosphere to obtain the main material LiNi 0.93 Co 0.03 Mn 0.04 O2;

[0116] (2) Take 12L of deionized water at a temperature of 0.5°C, add 1006.58g of lithium-containing compound lithium hydroxide monohydrate into the water, stir with a mechanical stirrer at 200rpm for 10min, and then add 20kg of the obtained main material LiNi 0.93 Co 0.03 Mn 0.04 O2, stir for 10 minutes to 0.93 Co 0.03 Mn 0.04A lithium hydroxide pre-coating layer is formed on the surface of O2, which is placed in a centrifuge and centrifuged at 50 Hz for 1 hour to obtain a centrifuge, which is then placed in a vacuum drying oven and dried at 120°C for 10 hours. After the material is completely dried, it is sieved with a 200-mesh sieve to obtain a pre-coated body;

[0117] (3) 15 kg of the pre-coated body was heat treated at 240° C. for 8 h in a mixed atmosphere of oxygen and ozone with a volume ratio of 90:10, so that the lithium hydroxide pre-coating layer was converted into a lithium peroxide coating layer, thereby obtaining a high-nickel ternary positive electrode material.

[0118] Example 2

[0119] This embodiment provides a high-nickel ternary material, including a main material, wherein the chemical formula of the main material includes LiNi 0.93 Co 0.03 Mn 0.04 O2, a coating layer is provided on the surface of the main material, and the coating layer is lithium peroxide;

[0120] In step (1) of the method for preparing the high-nickel ternary material, the mass of the lithium peroxide is adjusted from 19.8 g to 10 g. Except for the above, other conditions are exactly the same as those in Example 1.

[0121] Example 3

[0122] This embodiment provides a high-nickel ternary material, including a main material, wherein the chemical formula of the main material includes LiNi 0.93 Co 0.03 Mn 0.04 O2, a coating layer is provided on the surface of the main material, and the coating layer is lithium peroxide;

[0123] In step (1) of the method for preparing the high-nickel ternary material, the mass of the lithium peroxide is adjusted from 19.8 g to 39.7 g. Except for the above, other conditions are exactly the same as those in Example 1.

[0124] Example 4

[0125] This embodiment provides a high-nickel ternary material, including a main material, wherein the chemical formula of the main material includes LiNi 0.93 Co 0.03 Mn 0.04 O2, a coating layer is provided on the surface of the main material, and the coating layer is lithium peroxide;

[0126] In step (1) of the method for preparing the high-nickel ternary material, the mass of the lithium peroxide is adjusted from 19.8 g to 100 g. Except for the above, other conditions are exactly the same as those in Example 1.

[0127] Example 5

[0128] This embodiment provides a high-nickel ternary material, including a main material, wherein the chemical formula of the main material includes LiNi 0.93 Co 0.03 Mn 0.04 O2, a coating layer is provided on the surface of the main material, and the coating layer is lithium peroxide;

[0129] In step (2) of the method for preparing the high-nickel ternary material, the mass of the lithium-containing compound lithium hydroxide monohydrate is adjusted from 1006.58 g to 251.65 g. Except for the above, other conditions are exactly the same as those in Example 1.

[0130] Example 6

[0131] This embodiment provides a high-nickel ternary material, including a main material, wherein the chemical formula of the main material includes LiNi 0.93 Co 0.03 Mn 0.04 O2, a coating layer is provided on the surface of the main material, and the coating layer is lithium peroxide;

[0132] In step (2) of the method for preparing the high-nickel ternary material, the mass of the lithium-containing compound lithium hydroxide monohydrate is adjusted from 1006.58 g to 2516.46 g. Except for the above, other conditions are exactly the same as those in Example 1.

[0133] Example 7

[0134] This embodiment provides a high-nickel ternary material, including a main material, wherein the chemical formula of the main material includes LiNi 0.93 Co 0.03 Mn 0.04 O2, a coating layer is provided on the surface of the main material, and the coating layer is lithium peroxide;

[0135] In step (3) of the method for preparing the high-nickel ternary material, the volume ratio of oxygen to ozone is adjusted from 90:10 to 94:6. Except for the above, other conditions are exactly the same as those in Example 1.

[0136] Example 8

[0137] This embodiment provides a high-nickel ternary material, including a main material, wherein the chemical formula of the main material includes LiNi 0.93 Co 0.03 Mn 0.04 O2, a coating layer is provided on the surface of the main material, and the coating layer is lithium peroxide;

[0138] In step (3) of the method for preparing the high-nickel ternary material, the volume ratio of oxygen to ozone is adjusted from 90:10 to 98:2. Except for the above, other conditions are exactly the same as those in Example 1.

[0139] Example 9

[0140] This embodiment provides a high-nickel ternary material, including a main material, wherein the chemical formula of the main material includes LiNi 0.93 Co 0.03 Mn 0.04 O2, a coating layer is provided on the surface of the main material, and the coating layer is lithium peroxide;

[0141] In step (3) of the method for preparing the high-nickel ternary material, the volume ratio of oxygen to ozone is adjusted from 90:10 to 99:1. Except for the above, other conditions are exactly the same as those in Example 1.

[0142] Example 10

[0143] This embodiment provides a high-nickel ternary material, including a main material, wherein the chemical formula of the main material includes LiNi 0.93 Co 0.03 Mn 0.04 O2, a coating layer is provided on the surface of the main material, and the coating layer is lithium peroxide;

[0144] In step (1) of the method for preparing the high-nickel ternary material, the peroxide is adjusted from lithium peroxide to sodium peroxide, and the mass of the peroxide is adjusted from 19.8 g to 33.6 g. Except for the above, other conditions are exactly the same as those in Example 1.

[0145] Comparative Example 1

[0146] This embodiment provides a high-nickel ternary material, including a main material, wherein the chemical formula of the main material includes LiNi 0.93 Co 0.03 Mn 0.04 O2;

[0147] The method for preparing the high-nickel ternary material does not carry out step (2), and directly converts the main material LiNi obtained in step (1) into 0.93 Co 0.03 Mn 0.04 O2 performs step (3). Except for the above, other conditions are exactly the same as those in Example 1.

[0148] Comparative Example 2

[0149] This embodiment provides a high-nickel ternary material, including a main material, wherein the chemical formula of the main material includes LiNi 0.93 Co 0.03 Mn 0.04 O2;

[0150] The method for preparing the high-nickel ternary material does not carry out step (2) and step (3), and only uses the main material LiNi obtained in step (1) 0.93 Co 0.03 Mn0.04 O2, except for the above, other conditions are exactly the same as those in Example 1.

[0151] Comparative Example 3

[0152] This embodiment provides a high-nickel ternary material, including a main material, wherein the chemical formula of the main material includes LiNi 0.93 Co 0.03 Mn 0.04 O2;

[0153] In step (3) of the method for preparing the high-nickel ternary material, pure water is used to replace the lithium-containing aqueous solution. Except for the above, other conditions are exactly the same as those in Example 1.

[0154] Comparative Example 4

[0155] This embodiment provides a high-nickel ternary material, including a main material, wherein the chemical formula of the main material includes LiNi 0.93 Co 0.03 Mn 0.04 O2;

[0156] The method for preparing the high-nickel ternary material does not perform step (2) and step (3), but only performs step (1), and no peroxide is used in step (1). Except for the above, other conditions are exactly the same as those in Example 1.

[0157] The ternary materials obtained in the embodiments and comparative examples were tested:

[0158] Ⅰ. If Figure 1 As shown, Example 1 is a polycrystalline lithium nickel cobalt manganese oxide with no other impurities on the surface. Because the lithium hydroxide layer coated by water washing is very uniform, there is no obvious change in morphology after sintering in ozone. Figure 2 As shown, after water washing and ozone sintering treatment, the material is still lithium nickel cobalt manganese oxide with an α-NaFeO2 type layered structure, and the crystal structure has no obvious change.

[0159] Ⅱ. Detect the mass content of LiOH, Li2CO3 and residual lithium;

[0160] Specifically, 50 g of the ternary material was dispersed in 200 mL of deionized water, stirred for 15 min and filtered, and the filtrate was subjected to acid-base titration using 0.1 M hydrochloric acid solution in a potentiometric titrator, and the mass contents of LiOH, Li2CO3, and residual lithium were calculated according to the position of the jump peak.

[0161] III. Test the degree of lithium-nickel mixing in ternary materials;

[0162] Specifically, HighScore was used to refine the XRD data of the ternary material to obtain lithium-nickel mixed arrangement data.

[0163] IV. Test the discharge capacity and cycle performance of batteries made of ternary materials;

[0164] Specifically, the prepared high-nickel ternary positive electrode material was used as the active material, acetylene black was used as the conductive agent, and polyvinylidene fluoride (PVDF) was used as the adhesive in a mass ratio of 90:5:5 to make an electrode sheet. The electrode sheet was used as the positive electrode and the metal lithium sheet was used as the negative electrode to assemble a CR2430 button battery in a glove box filled with high-purity argon gas.

[0165] The electrical performance of the assembled batteries was tested using a Wuhan blue electric tester (CT2001A): the first-cycle capacity and first-cycle efficiency test conditions were: 2.8-4.25V, 0.1C (1C=180mA / g) for 1 cycle; the power-down cycle test conditions were: 2.8-4.25V, 0.1C for 2 cycles, followed by 2.8-4.25V, 0.5C for 80 cycles.

[0166] The results are recorded in Table 1.

[0167] Table 1

[0168]

[0169] In Table 1: “ / ” means not tested.

[0170] It can be seen from Table 1 that:

[0171] The peroxide content used in Example 1 is appropriate to reduce the degree of lithium-nickel mixing of the material, the water washing capacity concentration is moderate, the ozone concentration is high enough, and it has a higher capacity and better cycle performance. Figure 3 shown.

[0172] By comparing Example 1 with Examples 2-4, it is found that the higher the amount of peroxide added, the lower the lithium-nickel mixing value of the material.

[0173] Comparing Example 1 with Examples 5-6, it is found that after the lithium hydroxide concentration is reduced in Example 5, the LiOH content is significantly reduced, the discharge capacity is also significantly reduced, and the cycle performance is also poor. After the lithium hydroxide concentration is increased in Example 6, the LiOH content is significantly increased, and the residual lithium content is also very high, resulting in a low discharge capacity.

[0174] By comparing Example 1 with Examples 7-9, it is found that the discharge capacity decreases after reducing the ozone content because the lithium peroxide generated on the surface of the material decreases.

[0175] By comparing Example 1 with Example 10, it is found that in Example 10, the lithium peroxide in the high-temperature sintering is replaced with sodium peroxide. Because the sodium element will be washed away during the water washing process, the residual lithium on the surface of the material will be excessively washed away, thereby affecting the capacity.

[0176] Comparing Example 1 with Comparative Examples 1-4, it is found that the residual lithium in Comparative Example 1 is too high due to the lack of water washing process, which affects the capacity. Comparative Example 2 has poor capacity and cycle performance due to the lack of any modification.

[0177] From the above, it can be seen that the present invention can effectively reduce the degree of lithium-nickel mixing of materials by introducing peroxides during high-temperature calcination, coating the surface of the material with lithium-containing compounds during the water washing process, and further generating lithium peroxide to form a coating layer during sintering in an ozone-containing environment, thereby optimizing the material capacity and cycle performance. The high-nickel ternary positive electrode material prepared by the method of the present invention has a higher capacity and better cycle performance, and is suitable for application in the field of lithium-ion batteries.

[0178] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0179] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0180] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A high-nickel ternary positive electrode material, characterized in that: Including a main material, the chemical formula of the main material includes LiNi x Co y Mn z O2, wherein x≥0.6, y>0, z>0, x+y+z=1; a coating layer is provided on the surface of the main material, and the coating layer includes lithium peroxide.

2. The high-nickel ternary positive electrode material according to claim 1, characterized in that: The main material is an ultra-high nickel ternary positive electrode material, x>0.

9.

3. A method for preparing the high-nickel ternary positive electrode material according to claim 1, characterized in that: The preparation method comprises: (1) Ni x Co y Mn z (OH)2, mixed with lithium source and peroxide, calcined to obtain the main material LiNi x Co y Mn z O2, where x≥0.6, y>0, z>0, x+y+z=1; (2) The main material LiNi x Co y Mn z O2 is mixed with lithium-containing aqueous solution, and the main material LiNi x Co y Mn z A lithium hydroxide pre-coating layer is formed on the surface of O2 to obtain a pre-coating body; (3) The obtained pre-coated body is heat-treated in an ozone-containing atmosphere to convert the lithium hydroxide pre-coating layer into a lithium peroxide coating layer, thereby obtaining a high-nickel ternary positive electrode material.

4. The method for preparing a high-nickel ternary positive electrode material according to claim 3, characterized in that: In step (1), the precursor Ni x Co y Mn z The ratio of the molar amount of (OH)2 to the molar amount of lithium in the lithium source is 1:(1-1.2); Preferably, in step (1), the lithium source includes any one of lithium oxalate, lithium carbonate, lithium hydroxide monohydrate, lithium acetate or lithium citrate.

5. The method for preparing the high-nickel ternary positive electrode material according to claim 3 or 4, characterized in that: In step (1), the precursor Ni x Co y Mn z The ratio of the molar amount of (OH)2 to the molar amount of the peroxide is 1:(0.001-0.01); Preferably, in step (1), the peroxide comprises any one of lithium peroxide, sodium peroxide, nickel peroxide, strontium peroxide, or barium peroxide; Preferably, in step (1), the calcination temperature is 700-1100° C. and the calcination time is 10-20 hours.

6. The method for preparing a high-nickel ternary positive electrode material according to any one of claims 3 to 5, characterized in that: In step (2), the concentration of lithium in the lithium-containing aqueous solution is 0.5 to 5 mol / L; Preferably, the lithium-containing aqueous solution and the main material LiNi x Co y Mn z The mass ratio of O2 is (0.1-1):1; Preferably, the method for preparing the lithium-containing aqueous solution in step (2) comprises adding the lithium-containing compound to water at a temperature of 0 to 40° C. and stirring at 100 to 300 rpm for 2 to 20 minutes; Preferably, the lithium-containing compound includes at least one of lithium oxalate, lithium oxide, lithium hydroxide monohydrate, lithium acetate or lithium citrate.

7. The method for preparing a high-nickel ternary positive electrode material according to any one of claims 3 to 6, characterized in that: In step (2), the main material LiNi x Co y Mn z The time for mixing O2 and lithium-containing aqueous solution is 10 to 60 minutes; Preferably, in step (2), the main material LiNi x Co y Mn z After O2 is mixed with the lithium-containing aqueous solution, the mixed solution is centrifuged at 40-60 Hz for 0.5-1.5 hours to obtain a centrifuge; the centrifuge is vacuum dried at 100-180°C for 2-20 hours, and then passed through a 280-320 mesh sieve to obtain a sieve-less material; the sieve-less material obtained is used as the pre-coated body to perform step (3).

8. The method for preparing a high-nickel ternary positive electrode material according to any one of claims 3 to 7, characterized in that: In step (3), the volume of ozone in the ozone-containing atmosphere is 1% to 10%; Preferably, the heat treatment is performed at a temperature of 200 to 400° C. and for a time of 5 to 10 hours.

9. A positive electrode sheet, characterized in that: Contains the high-nickel ternary positive electrode material as claimed in claim 1 or 2.

10. A battery, characterized in that: A positive electrode sheet comprising the positive electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Sintering process of high-stability lithium ion high-nickel positive electrode material

    CN110330059A

  • Composite cathode material and preparation method and application thereof, and lithium ion battery

    CN112271281A

  • Lithium supplementing method for coated high-nickel ternary positive electrode material

    CN114864947A

  • Photoresist transferring resin for LED chip transferring, LED chip transferring method using photoresist transferring resin and manufacturing method of display apparatus using the same

    KR102218988B1

  • Lithium metal composite oxide powder and positive electrode active material for lithium secondary battery

    US20220173392A1

Cited By

  • High-capacity high-nickel ternary positive electrode material, preparation method thereof and lithium ion battery

    CN121687899A